Faktor-faktor determinan penyebab loss to follow up pada orang dengan HIV dan AIDS (ODHA) yang menerima terapi Antiretroviral (ARV) - Rahmat Kurniawan; Rita Dwi Pratiwi; Suyono Suyono (Holistik Jurnal Kesehatan, 2022)
Background: Based on data from the Tangerang District Hospital in October 2020, it was found that data on follow-up under antiretroviral therapy (ARV) among people living with HIV/AIDS (PLWHA) during the pandemic period for the last 3 months from February to April 2020 showed a decrease in the number but had a fluctuating graph in taking drugs every month, reaching 1012 patients, of which 20% were children. In addition, during the pandemic, there was an increase in LFU (lost to follow-up) cases of ARV treatment regimens.Purpose: To identify determinant factors of loss to follow-up under antiretroviral therapy (ARV) among people living with HIV/AIDS (PLWHA)Method: A quantitative research with a cross-sectional approach. The number of samples in this study was 45 respondents. The analysis used is univariate and bivariate. The statistical tests used are Chi-Square test and logistic regression.Results: Finding that the factors related to the cause of the withdrawal of ARV drugs were health insurance, side effects of ARVs, CD4 values, family support, hopelessness, stress levels, and self-esteem. Then a logistic regression test was carried out to find out which factor had the most influence and the results showed that the CD4 value was the most significant indicator with an OR (Odds Ratio) value of 26,812 812, meaning that people living with HIV who had CD4 values < 200 had a 26,812 times greater risk of dropping out of ARV drugs, compared to people living with HIV who have CD4 values 200.Conclusion: CD4 value is the most significant factor in the incidence of ARV drug withdrawal in living with HIV.Keywords: Loss to follow-up; Antiretroviral therapy (ARV); People living with HIV/AIDS (PLWHA)Pendahuluan: Berdasarkan data RSUD Kab.Tangerang Oktober 2020 didapatkan data follow up pada orang dengan HIV dan AIDS (ODHA) yang menerima terapi Antiretroviral (ARV selama masa pandemi 3 bulan terakhir Februari-April 2020 menunjukan penurunan angka follow up  namum memiliki grafik fluktuatif dalam pengambilan obat tiap bulan mencapai 1012 pasien dimana 20% termasuk usia anak. Selain itu, selama pandemi terjadi peningkatan kasus LFU (lost to follow up) dari regiment pengobatan ARV.Tujuan: Mengidentifikasi faktor-faktor determinan penyebab loss to follow up pada orang dengan HIV dan AIDS (ODHA) yang menerima terapi Antiretroviral (ARV)Metode: Penelitian kuantitatif dengan pendekatan cross sectional. Jumlah sampel dalam penelitian ini 45 responden. Analisis yang digunakan adalah univariat dan bivariat. Uji statistik yang digunakan yakni, uji Chi Square dan regresi logistik.Hasil: Didapatkan bahwa faktor yang berhubungan dengan penyebab loss to follow up ARV adalah jaminan kesehatan, efek samping ARV, nilai CD4, dukungan keluarga, keputusasaan, tingkat stress, dan harga diri. Selanjutnya dilakukan uji regresi logistic untuk mendapatkan faktor mana yang paling berpengaruh dan didapatkan hasil bahwa nila CD4 merupakan indicator paling bermakna dengan nilai OR (Odds Rasio) sebesar 26.812 812 artinya ODHA yang memiliki kadar nilai CD4 < 200 memiliki risiko 26.812 kali lebih besar penyebab loss to follow up ARV dibandingkan dengan ODHA yang memiliki kadar nilai CD4 ≥ 200.Simpulan: Nilai CD4 merupakan faktor yang paling bermakna terhadap kejadian loss to follow up  ARV pada ODHA.